Answer:
-117
Explanation:
To find f(-4)-f(9), we must find the values of f(-4) and f(9) first. In order to do that, we'll have to plug in -4 and 9 individually in the function f(x)=2x^2-x (or in your words, f(x)-2xsquared-x).
Let's start with -4.
f(x)=2(-4)^2-(-4)
f(x)=2(16)+4
f(x)=32+4
f(x)=36
We have the value pf f(-4) now, so let's move on to 9.
f(x)=2(9)^2-9
f(x)=2(81)-9
f(x)=162-9
f(x)=153
We have the value of f(9) too now. Let us proceed to find f(-4)-f(9).
Substitute our found values into it.
36-153=-117
-117 is the result of f(-4)-f(9).